Art as the Energy of Life Creative Process Representation of Sasak Womanhood in Visual Media - Lucky Wijayanti (Graduate School of Institut Seni Indonesia Yogyakarta, 2014)
The idea of creation/formulation of the problem in the dissertation of art creation is the reality of women workers to the nature of femininity in performing arts as interpreted life energy into the problems of women workers. The idea is then formulated into the concept of creation, the role of women as the guardian of the family, gave birth to progeny, and the resilient nature of women as breadwinners for survival, even more importantly women as keepers of tradition. Through the creative process to create works of art by presenting a ‘rasa’ that can be captured and responded to by the brain into something that essence and recorded in the memory, (VS Ramachandran, 2012). The study was conducted using visual aesthetic and creative through the photographic process with the exploration of materials such as: objects generated tradition of Lombok, for example woven fabrics, woven and the other as an aesthetic element as well as elements of art such as: shape, line, color, shape, composition, and texture. As for all stages of the process based on the embodiment of the work of the working stages of the creative process by Csikszentmihalyi (1996), namely: preparation, incubation, insight / arcing ideas, evaluation, development, and presentation in the form of art exhibitions. In general it can be concluded, that in this aspect of the subject matter of the concept of women in the end that guarantees life for themselves women are women themselves. In the form of work, technical realization through the creative process with visualization methods.